Influence of vermicompost and npk on the growth and protein content of boro rice (Oryza sativa L.) - Nishi, KN; Rahman, S; Nakamura, K; Rahman, MK (Journal of Biodiversity Conservation and Bioresource Management, 2020)
Influence of vermicompost (2.5, 5, 7.5 and 10 ton/ha), Nitrogen (12, 24, 36, 48 and 60 kg/ha), phosphorus (4, 8, 12, 16 and 20 kg/ha) and potassium (10, 20, 30, 40 and 50 kg/ha) on the growth and protein contents of Boro rice (Oriza sativa L.) was examined. Highest height (93.03cm), leaf number (23 no/plant), highest productive plants observed (8.67 no/pot), vegetative plants (8.0 no/pot), dry weight of panicle per plant (9.45 g), length of panicle (22.37 cm), number of grains per panicle (153.33),1000-grain weight (21.56 g) and the maximum dry weight (28.15 g/plant) were observed in VC10 ton/ha + N12P4K10 kg/ha treatments. Highest concentrations of protein content (29.875%), P (0.478%), K (5.20%) and S (0.182%) were in N60P20K50 kg/ha. Results showed that the overall best growth performance and yield were achieved in VC10 ton/ha + N12P4K10 kg/ha treatments. J. Biodivers. Conserv. Bioresour. Manag. 2019, 5(2): 69-74